Effects of Services Quality on Customer Satisfaction: A Case from Private Hostels in Wa-Municipality of Ghana - Karikari Appiah, Michael (British Journal of Marketing Studies, 2016)
The aim of this was to examine the influence of Hostel Services Quality on Student’s Satisfaction in the University of Development Studies (UDS) within the Wa-municipality of Ghana. A cross sectional quantitative research design was employed. The target populations of the study were predominately students in private hostels. Whopping 300 students were randomly sampled to participate in the study.  The questionnaires were adopted from the SERQUA Model. Both primary and secondary data were employed in the study. The data were analyzed with the aid of Statistical Package for Social Science (SPSS). The study had revealed that overall the model used in this study was acceptable ANOVA was significant (p-value < 0.05). The study also revealed that, taking all the other factors constant at zero; a unit change in tangibility will bring 0.054 change in students satisfaction, a unit change in assurance will bring 0.318 a unit change in reliability will bring 0.342 in customer satisfaction, a unite change in responsiveness will bring 0.096 change in students satisfaction and finally, a unit change in empathy will bring 0.381 change in students satisfaction. It is concluded that hostel management should paid attention to the legitimate discontent among the students to improve efficiency in order to prevent massive switching rate in the long run when supply exceed demand in this business.